Preparation and Characterization of Decellularized Caprine Periosteum Scaffolds for Fracture Gap Healing - Goyal, Ravi P.; Gangwar, Anil K.; Khangembam, Sangeeta D.; Yadav, Vipin K.; Singh , Yogendra; Kumar, Prafull (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Certain chemical and enzymes like sodium deoxycholate, sodium dodecyl sulphate and Triton X-100 have been used as biological  detergents but are responsible for residual cytotoxicity in the decellularized extracellular matrix. The periosteum plays a key role in  bone regeneration. We aimed to prepare decellularized caprine periosteum scaffold by exploring the decellularization property of  Sapindus mukorossi fruit pericarp extract (SPE). We developed decellularization protocols to completely remove the periosteum cellular  components and for good maintenance of the hierarchical multilayer structures and components of the extracellular matrix (ECM) with  no cytotoxicity. Histological analysis of hematoxylin and eosin and Masson’s trichrome stained tissue samples decellularized by 5%  SPE extract confirmed decellularization with preservation of extracellular matrix microarchitecture. DAPI stained decellularized tissues  revealed complete removal of nuclear components, verified by DNA content measurement. It was concluded that 5% SPE is ideal for  preparation of decellularized caprine periosteum scaffold and these scaffolds can be used for bone regeneration.
Keywords: Caprine periosteum; DAPI staining; Decellularization; Sapindus mukorossi